Cloning and sequence analysis of E0 gene of virulent classical swine fever virus isolates in Shaanxi Province in 2006 — 2007 - WU Xu-jin; ZHU Xiao-fu; CHEN De-kun (浙江大学学报. 农业与生命科学版)
According to the published genetic sequences of reference strain Shimen on GenBank, two pairs of primers were synthesized to amplify the E0 gene of nine prevalent virulent classical swine fever virus (CSFV) isolates from swine samples in Shaanxi Province by reverse transcription-nested polymerase chain reaction (nested RT-PCR). The nucleotide and amino acid sequences of these isolates were also compared and analyzed with reference strains ALD, Alfort187, Brescia, C HVRI, CAP, Shimen, GXWZ02 and HCLV. The nucleotide analysis showed that these nine isolates could be divided into two groups, one of them (LN163) belonged to group I sharing 80.8% -82.4% homology, while the other eight isolates belonged to group II sharing 93.6% -99.6% homology with reference strains within respective groups. Amino acids sequences analysis indicated that these nine isolates developed two different evolving branches, the strain LN163 of which shared 83.9% homology and the other eight isolates shared 94.4% -98.1% homology compared with the reference wild strain GXWZ02 from China, and these nine field isolates had obvious variation for the 88.0% -89.5% and 89.1% -91.8% homology of amino acids sequences compared with HCLV and Shimen, respectively.